2018
DOI: 10.21608/zjar.2018.48570
|View full text |Cite
|
Sign up to set email alerts
|

The Main Sucking Insect Pests and Their Associated Predators on Okra Plants

Abstract: The present study was conducted to survey and evaluate the population densities of the major sucking insect pests infesting okra plants and their common associated predators and its relation with the prevailing temperature and relative humidity at Diarb-Nigm district, Sharkia Governorate, Egypt during the two summer growing seasons of 2015 and 2016. Bemisia tabaci (Gennadius), Oxycarenus hyalinipennis Costa, Aphis gossypii Glover, Empoassca lybica (Bergevin) and Thrips tabaci Linde were the main sucking insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…These results are supported by the findings of Hammad and Mohsen (2000) who stated that the maximum numbers of the cotton aphid on roselle plants were recorded in July and August during the two summer growing seasons of 1997 and 1998. The obtained data are also partially agree with those of Ismail (2018) who studied the incidence of the major sucking insect pests on okra plants during 2015 and 2016 seasons and reported that the main activity period of cotton aphid was in July and August in both seasons of the study, And Pathon et al (2018) who found that A. gossypii showed a high level of infestation on okra plants in August during 2015 and 2016 growing seasons.…”
Section: Population Fluctuation Of the Cotton Aphid Aphis Gossypii (Glover) On Roselle Plantssupporting
confidence: 89%
See 1 more Smart Citation
“…These results are supported by the findings of Hammad and Mohsen (2000) who stated that the maximum numbers of the cotton aphid on roselle plants were recorded in July and August during the two summer growing seasons of 1997 and 1998. The obtained data are also partially agree with those of Ismail (2018) who studied the incidence of the major sucking insect pests on okra plants during 2015 and 2016 seasons and reported that the main activity period of cotton aphid was in July and August in both seasons of the study, And Pathon et al (2018) who found that A. gossypii showed a high level of infestation on okra plants in August during 2015 and 2016 growing seasons.…”
Section: Population Fluctuation Of the Cotton Aphid Aphis Gossypii (Glover) On Roselle Plantssupporting
confidence: 89%
“…Also Abdel Moniem and Abd El-Wahab (2006) who mentioned the importance of predators as a biological control agent in detecting the population of insect pests infesting some medicinal plants. And Ismail (2018) who stated that the meteorological parameters are the main variable factors that affect population fluctuation of sucking insect pests.…”
Section: Mean Temperaturementioning
confidence: 99%
“…Also, the highest average numbers of the green leafhopper were recorded on squash plants occurred on 3 rd and 2 nd weeks of October (40.67 and 43.00) during 2018 and 2019 growing seasons, respectively, and the highest average numbers monthly of E. decipiens were 146.67 recorded during October followed by 93.67 in November and 28.66 in December; and 156.00 recorded during October followed by 106.00 in November and 37.00 in December during 2018 and 2019 successive seasons, respectively. The present results are in harmony with those obtained by, Metwally et al (1995) stated that the initial appearance of the green leafhopper, E. decipiens varied from one year first and second seasons, 1991 and 1992 on squash plants, the seasonal activity of jassid was restricted in the second half of summer squash growing season of 1992; Abdalla & Al-Habashy (2013) who indicated that, one peak occurred at the 2 nd week of March for jassid on the broad bean during 2011 and 2012 seasons; Awadalla et al (2018) who stated that the highest relative abundance of E. decipiens occurred in March plantation on squash plants during 2014 and 2015 successive seasons, and Ismail (2018) who revealed that the jassid E. lybica peaked in the 3 rd week of July, 4 th week of August and 2 nd week of September during 2015 growing season, while in the season of 2016 it peaked in the 2 nd week of August and 1 st week of September occurred on okra plants.…”
Section: -Nili Plantationmentioning
confidence: 99%